Edukasi dan Sosialisasi Penyakit Gagal Ginjal Kronik pada Remaja “Sebuah Kewaspadaan Dini dalam Pencegahan Penyakit Ginjal” - Wijianto Wijianto; Sri Musriniawati Hasan; Djadid Subchan; Evelin Kalaha; Nur Eli Asomah (Poltekita: Jurnal Pengabdian Masyarakat, 2025)
Non-communicable diseases (NCDs) such as diabetes, hypertension, kidney failure and heart disease are increasingly becoming a serious threat throughout the world, including in Indonesia. Kidney failure is a non-communicable disease with increasing morbidity and mortality. NCDs (kidney failure) usually appear without symptoms and do not show any specific clinical signs, so that most people are not aware of the dangers of NCDs. Early detection and prevention efforts for kidney failure are very important because kidney failure in children and adolescents can have a negative impact on future life. This community service aims to conduct early detection screening for risk factors for kidney failure and health education to increase knowledge about NCDs. The method used in this activity is education and socialization of Kidney Failure Disease in adolescents at SLTA N 3 Luwuk. The targets involved in this activity were more than 100 people. The results of the pre-test and post-test activities on participants showed an increase in test scores before and after receiving education. The average pre-test score of participants was 7.55 with SD 0.202, in the post-test the average score was 9.72 with SD 0.521. From these results, it can be seen that there was an increase in score of 2.17 points. The results of the statistical test obtained a p value of 0.000, which means that there is a significant difference between the scores before (pre-test) and after education (post-test). This community service activity is an important promotive and preventive step in improving public health, especially for adolescents in efforts to prevent and overcome kidney failure.